SELIDIK CEPAT CIRI AIR TANAH YANG TERCEMAR (KAWRUH TIRTA) DI FORUM KOMUNIKASI WARGA BUDAYA JAWA NGUDI KAWRUH JAWA, MRANGGEN, SEWON, BANTUL - Arie Noor Rakhman (DHARMA BAKTI, 2020)
Groundwater condition in several locations in Mranggen area, Banjarharjo Village, Sewon District, Bantul Regency are very clear, but the results of laboratory analysis state that it is unsuitable for consumption. This has been increasingly felt since the earthquake in 2006. This community service activity aims to reintroduce the way to quickly investigate polluted groundwater using tea water. Community service methods that have been carried out through counseling at the Ngudi Kawruh Java Culture Citizens Communication Forum. The results of the counseling found residents were able to re-recognize the culture of local wisdom, namely the application of the science of finding the right water source (Javanese: kawruh tirta) when making wells using the tea water method. From the results of re-analysis in the laboratory again found that groundwater in this area contains manganese (0.27 mg / l), exceeding the threshold (0.1 mg / l) with a neutral water pH (6.8). This indicates that groundwater in this area is indeed not suitable for drinking. Further treatment is needed to make it drinkable, namely by the reverse osmosis method. This method has been believed to be able to minimize the manganese content in groundwater by 90%.